2012
DOI: 10.1111/j.1365-4632.2011.05291.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha promoter‐308G/A polymorphism in Mexican patients with patchy alopecia areata

Abstract: Our data suggest that there is a plausible association between the presence of the TNFα-308G/A polymorphism and a higher susceptibility for developing patchy AA. This risk might be due to overproduction of TNFα, which would facilitate an autoimmune response against the hair follicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…In this study, an association between rs1800629 of the TNFα-308G/A and AA was confirmed ( P = 0.022) and found to be consistent with the results of Gregoriou et al13 It is also consistent with another study performed by Cristina et al in Mexico which suggested a credible association between the presence of TNFa-308G/A polymorphism and an increased susceptibility for the development of patchy AA 23. This overproduction of T NFα might lead to a higher risk of facilitating an autoimmune response against the hair follicle.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, an association between rs1800629 of the TNFα-308G/A and AA was confirmed ( P = 0.022) and found to be consistent with the results of Gregoriou et al13 It is also consistent with another study performed by Cristina et al in Mexico which suggested a credible association between the presence of TNFa-308G/A polymorphism and an increased susceptibility for the development of patchy AA 23. This overproduction of T NFα might lead to a higher risk of facilitating an autoimmune response against the hair follicle.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of allele –308A was not higher than 10% in Mestizos. This polymorphism seems to be very similarly distributed among Mexicans , and in general, for some Latin‐American populations, such as Colombians, Venezuelans, and Argentineans , with only two exceptional Mexican cases, in which allele A accounted for 20% of the frequency in individuals from the state of Nuevo Leon and Mexico City . Moreover, in European and African populations, the frequency of this allele ranges from 5% to 23% ; in particular, in the Spanish and the Portuguese, these values reach 15% and 24%, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…19 In one study, a tumour necrosis factor-a gene polymorphism (-308 G/A) confered increased susceptibility for the development of patchy alopecia areata. 20 The present study investigated polymorphisms in the genes for the cytokines IL-12, IL-17 and IL-23. To the best of our knowledge, this is the first study to investigate IL12 and IL23R gene SNPs in alopecia areata.…”
Section: Discussionmentioning
confidence: 99%